The Influence of Lampungnese Ethnicity Accent on Dialect to Lampungnese Students’ Pronunciation Ability in Cross Culture Understanding Class - Fatma Yuniarti; Sutarno Sutarno (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2019)
Article Withdrawn